Simple shear response of a thin sheet of polytetrafluoroethylene under large deformations. (September 2019) - Filho, J.C.A.D.; Nunes, L.C.S.
Abstract: Rigid-body motions and deformations of a thin sheet of polytetrafluoroethylene (PTFE) under simple shear at large deformations were experimentally investigated. The Modified slotted shear test was performed under quasi-static conditions at constant temperature. A new approach was developed to improve the accuracy of measurements in five sub-regions along shear path of each specimen. The proposed approach consisted of three main steps: estimation of displacement fields, determination and removal of translational and rotational motions and evaluation of pure deformations. Displacement fields were obtained using the Digital Image Correlation (DIC) method. Amount of shear, normal extensions, principal stretches and principal directions were evaluated from pure deformations using the displacement fields. Results showed that all sub-regions did not exhibit considerable rotations for values of amount of shear up to 0.4. A contraction of the analyzed regions at the same direction of the applied loads was observed, while the normal extension remained almost unchanged in the direction perpendicular to the applied loads. For sub-regions near notch tips at large values of amount of shear, angle of rotation of 5° and 10% of contraction were observed. Overall, the influence of rigid-body motions and normal extensions on the principal stretches and principal directions was relatively small, mainly in the middle of the specimen. Moreover, a simple constitutive model was used to describe the shear response of PTFE. Highlights: Investigation of rigid-body motions and deformations of PTFE specimens under simple shear. New approach to improve the accuracy of measurements using modified slotted shear test. For values of amount of shear up to 0.4, rotations and normal extensions are relatively small. Alternative constitutive model for describing the shear response of PTFE. Combination of the slotted shear test and the proposed approach using DIC method can be a powerful tool.